Psychosocial Research and Practice: a Re-view - Stella Brandão Goulart, Maria; Ferreira Amaral Gomes, Leísa; Pereira Ribeiro, Listhiane (Revista Pesquisas e Práticas Psicossociais, 2017)
Social Psychology is a rapidly developing area and it is fundamental to analyze how and through which paths its scientific production is taking shape. The objective of this article is to share conclusions of the research “Estado da Arte em Psicologia Social em Minas Gerais" ("The State of the Art in Social Psychology"), whose general objective was to map the production on Social Psychology in this Brazilian state at present, through the analysis of some discursive corpora, such as annals of events and specialized journals. The methodology consists in content analysis associated with a phenomenological reading, considering the subjectivity and comprehension capacity of the interpreter team. The review results of the semiannual journal “Pesquisas e Práticas Psicossociais” ("Psychosocial Research and Practices") from the Federal University of São João del-Rei 2007/2008 will be presented. The results set a parameter for reflection on the construction of the Social Psychology field, denoting its multiplicity. Key words: Social Psychology; Content Analysis; Researches; Practices.